Chronic Respiratory Disease (Crd) of Chicken - Soeripto . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2009)
Chronic respiratory disease (CRD) of chicken is the most costly disease confronting poultry industries in the world. The economic losses due to CRD was estimated up to billions rupiahs per year in Indonesia, and in the USA was estimated up to hundred millions dollars per year. The losses mainly due to decreases of body weight gain, egg production, feed efficiencies, hatchabilities and  increases  of  embryo  mortality.  The  main  causative agent  of  CRD  is Mycoplasma  gallisepticum (MG). Respiratory disturbances, excretion of nasal exudate, coughing, sneezing and hyperaemic of the conjunctiva are very often seen as the clinical signs. Pathological lesions are often found as inflammation of respiratory organs and more specific lesions are seen as inflammation and thickening of the airsac membranes with foci cheesy materials scattered around the airsacs. Diagnosis of CRD can be made by clinical symptoms, serology examination dan isolation of MG. Treatment, prevention and controls of CRD have been carried out for years, but cases of CRD are still present up to now. The MGTS11 vaccine as the third generation of CRD vaccine was reported to be effective for controlling CRD of chickens and potentially used as a tool for eradication programme of CRD in the future.   Key words: Chronic respiratory disease, chicken